DOES “GLASS CEILING” OR “SLIPPERY LADDER” LEAD TO THE SCARCITY OF WOMEN IN ACADEMIC LEADERSHIP? AN APPROACH OF Q-METHODOLOGY - Hong, Lily Hue (PEOPLE: International Journal of Social Sciences, 2018)
Gender equality and gender parity has been the central issue for countries. Lack of senior women leaders, in general, frequently been the heated subject of debate in many countries and Vietnam is no exception. Despite of recently women have made great contributions both in the academia and social life, they still remain underrepresented in the top levels of leaders both in public administration and higher education institutions. This study aims to explore the main reasons leading to the scarcity of women in academic leadership, in the case of Vietnam National University Ho Chi Minh city (VNU-HCM). Based on using the Q methodology-introduced by William Stephenson in 1935, this study asked eighteen women of VNU-HCM to rank-order a set of different forty statements about causes limited the advancement opportunities of women from “most disagree” to “most agree”. By identifying disagreement and consensus among participants, four diverse perspectives on the root causes for the persistence of gender inequality at the highest ranks of academic leadership were uncovered including factor 1 - family orientation, factor 2- alternative choices, factor 3- traditional cultural social values, and factor 4- workplace attitude and structure. This study also finds out that most of female managers at the VNU-HCM maybe face ‘slippery ladder” than a “glass ceiling” because they by themselves skip the advancement opportunities.